2019
DOI: 10.1093/nar/gkz253
|View full text |Cite
|
Sign up to set email alerts
|

Predictive models of eukaryotic transcriptional regulation reveals changes in transcription factor roles and promoter usage between metabolic conditions

Abstract: Transcription factors (TF) are central to transcriptional regulation, but they are often studied in relative isolation and without close control of the metabolic state of the cell. Here, we describe genome-wide binding (by ChIP-exo) of 15 yeast TFs in four chemostat conditions that cover a range of metabolic states. We integrate this data with transcriptomics and six additional recently mapped TFs to identify predictive models describing how TFs control gene expression in different metabolic conditions. Contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 42 publications
1
32
1
Order By: Relevance
“…We also ran DTO on ChIP-exo data from yeast (Rhee and Pugh 2011;Bergenholm et al 2018;Rossi et al 2018a,b;Holland et al 2019). Twenty TFs had data in ChIP-exo, Harbison ChIP-chip, TFKO, and ZEV15, enabling all-way comparisons.…”
Section: In Yeast Chip-exo Yields Better Convergence Than Traditionamentioning
confidence: 99%
See 1 more Smart Citation
“…We also ran DTO on ChIP-exo data from yeast (Rhee and Pugh 2011;Bergenholm et al 2018;Rossi et al 2018a,b;Holland et al 2019). Twenty TFs had data in ChIP-exo, Harbison ChIP-chip, TFKO, and ZEV15, enabling all-way comparisons.…”
Section: In Yeast Chip-exo Yields Better Convergence Than Traditionamentioning
confidence: 99%
“…The "25&37C merged MockIP controls" file was obtained from the authors. ChIP-exo data for 26 TFs were compiled from several studies (Rhee and Pugh 2011;Bergenholm et al 2018;Rossi et al 2018a,b;Holland et al 2019). We obtained data directly from the authors of Holland et al (2019) and Bergenholm et al (2018) and focused on the glucose-limited chemostat data as that gave the best agreement with both TFKO and ZEV15 response data (Supplemental Fig.…”
Section: Yeast Binding Location Data Setsmentioning
confidence: 99%
“…We anticipate improvements coming from better network maps. One likely source of better maps is new, more accurate methods for measuring TF binding locations (53,(75)(76)(77)(78). The input network could also be improved by obtaining TF perturbation data from cells grown in new conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study from our lab, in which we used high resolution chromatin immunoprecipitation followed by exonuclease treatment and sequencing (ChIP-exo), we observed that Leu3 showed differential binding behavior at four different cultivation conditions, covering respiratory and fermentative growth (Holland et al . 2019 ). The four conditions were, however, so different that it was difficult to assess if this change in binding behavior was connected to changes in leucine availability or caused by other effects.…”
Section: Introductionmentioning
confidence: 99%